2021
DOI: 10.7717/peerj.12197
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics-based analyses of KPNA2 highlight its multiple potentials in hepatocellular carcinoma

Abstract: Dysregulation and prognostic roles of Karyopherin α2 (KPNA2) were reported in many malignancies including hepatocellular carcinoma (HCC). A multi-omics analysis of KPNA2 is needed to gain a deeper understanding of its multilevel molecular characteristics and provide novel clues for HCC diagnosis, prognosis, and target therapy. Herein multi-omic alterations of KPNA2 were analyzed at genetic, epigenetic, transcript, and protein levels with evaluation of their relevance with clinicopathological features of HCC by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…YBX1 participates in diverse biological processes and possesses the capacity to modulate a broad spectrum of genes that govern cell proliferation, cell viability, resistance to drugs, and instability of chromatin [ 86 ]. Karyopherin α2 (KPNA2), a protein implicated in the conventional pathway of nuclear protein transportation, has been observed in many instances of cancer, including HCC [ 87 , 88 ], Nevertheless, the exact molecular mechanisms responsible for the function of KPNA2 are still not fully understood. Previous studies have shown that KPNA2 promotes the advancement of HCC by interfering with the cell cycle and increasing the expression of CCNB2 (cyclin B2)/CDK1 (cyclin-dependent kinase 1).…”
Section: Discussionmentioning
confidence: 99%
“…YBX1 participates in diverse biological processes and possesses the capacity to modulate a broad spectrum of genes that govern cell proliferation, cell viability, resistance to drugs, and instability of chromatin [ 86 ]. Karyopherin α2 (KPNA2), a protein implicated in the conventional pathway of nuclear protein transportation, has been observed in many instances of cancer, including HCC [ 87 , 88 ], Nevertheless, the exact molecular mechanisms responsible for the function of KPNA2 are still not fully understood. Previous studies have shown that KPNA2 promotes the advancement of HCC by interfering with the cell cycle and increasing the expression of CCNB2 (cyclin B2)/CDK1 (cyclin-dependent kinase 1).…”
Section: Discussionmentioning
confidence: 99%